Mother-infant postnatal experience and its association with maternal emotion and coping during the COVID-19 pandemic - Nasri, Nuruljannah Mohamad; Gan, Wan Ying; Mohd Shukri, Nurul Husna (Routledge, 2024)
The COVID-19 pandemic resulted in a partial lockdown in Malaysia known as Movement-Controlled-Order (MCO), which has affected primary care management and social life norms. Thus, psychological health is a concern for mothers, particularly during the postpartum period. This study aimed to determine factors associated with maternal emotional experiences and coping during the pandemic.